Arsenic contamination of Bangladesh aquifers exacerbated by clay layers - Ivan Mihajlov (Nature Portfolio, 2020)
Generally it is thought that confining clay layers provide protection to low-arsenic groundwaters against intrusion of shallower, high-arsenic groundwater bodies. Here, the authors show that impermeable clay layers can increase arsenic input to underlying groundwater systems due to reduction of iron oxides coupled to carbon oxidation.